Estudo da remoção de zinco e de álcalis contidos em lamas de aciaria LD - Marcos Vinicius Cantarino (2011)
Fine and coarse fractions of BOF sludge are collected through the gas cleaning system of the LD steel plant in the LD steel production route. In the industrial unit of ArcelorMittal Monlevade, the generation of these residues varies from 5.6 to 7.2 kg/t of crude steel for the BOF coarse sludge and from 17.0 to 22.8 kg/t of crude steel for the fine sludge. Due to its content of total iron, around 50-60%, these residues could be recycled into the production process of sinter. However, for such application, theircontent of zinc and alkalis must be significantly reduced as they contribute to damage the refractory of the Blast Furnace, increase heat losses and increase consumption of coke. Analysis of Eh vs pH diagrams indicate that zinc could be selectively leached using alkaline solutions. But X-ray analysis revealed that zinc is predominantly found asZnO and ZnO.F2O3 (zinc ferrite) in the BOF sludge. Because zinc ferrite is insoluble in NaOH solutions, it is necessary to decompose it by heating operation and then submit the BOF sludge for the zinc leaching step, which is recovered by chemical precipitation. In this work, the main operating variables of a hybrid route consisting of steps roastleaching-precipitation were studied, aiming to remove zinc and alkalis from BOFsludges. The operating variables studied in the roast step were temperature, time and Sludge/NaOH ratio, while in the leaching step the effect of temperature, time, NaOH concentration and solid/liquid ratio were studied. Two by-products were obtained in this work: (i) Treated BOF sludge rich in iron and with 95% of zinc removal without alkali to be submitted for blending and recycling operation in the sinter, and (ii) zinc removed from the sludge with 96% of efficiency that was precipitated as hydroxide for further applications